A secured federated learning system leveraging confidence score to identify retinal disease - Eshan, M Sakib Osman; Nafi, Md. Naimul Huda; Sakib, Nazmus; Maruf, Md. Ahnaf Morshed; Emon, Mehedi Hasan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.